Investigating the Correlation Between the Use of AI Writing Tools and EFL Essay Writing Performance - Faadhilah, Nuha; Susilawati, Endang; Sumarni, Sumarni (Universitas Pahlawan Tuanku Tambusai, 2025)
The growing integration of AI writing tools in education raises concerns about their influence on EFL students’ writing development. Empirical evidence is scarce, despite the assumptions regarding their advantages. This study investigated the correlation between the utilization of AI tools and essay scores among 23 fourth-semester students enrolled in the English Language Education Study Program at FKIP UNTAN (A1 class, 2024/2025). The data was obtained by distributing a questionnaire regarding the frequency of AI usage and scoring essays using a validated rubric. Pearson's correlation analysis revealed a non-significant, weak correlation (r = -0.078, p = 0.723). Grammarly and QuillBot were frequently employed to enhance grammar, clarity, and coherence, as evidenced by qualitative data. The findings challenge the assumption that the direct improvement of essay quality is an outcome of frequent use of AI tools, suggesting that other factors have a more significant impact on writing outcomes.